Enhancement of Load Carrying Capacity of Steel Tubular Columns In-filled with Fibre Reinforced Concrete - Mohanraj, E.K.; Ravisankar, K.L.; Karthika, P.; Manikandan, Dr.P. (International Journal of Psychosocial Rehabilitation, 2019)
Steel members have the advantages of high tensile strength and ductility, while concrete members have the advantages of high compressive strength and stiffness. Steel - Concrete composite members, resulting in a member that has the valuable qualities of materials. In this paper, an attempt was made with steel tubular columns in-filled with fibre reinforced concrete and normal conventional concrete so as to improve the strength of tubular columns in construction works. The performance of circular and square concrete-filled steel tubular sections (CFSTs) with and without fibre under axial load is presented. The effects of steel tube dimensions, shapes and the strength of concrete are examined. Recorded column strengths are compared with the values predicted by Eurocode 4. 12 specimens were tested with strength of concrete as 20 MPa and a D/t ratio 22.3, 23.7 & 25.4. The columns were 76.1 & 88.9 mm in diameter and 72.0 & 91.5 mm in square are 900 mm in length. From the test results it was observed that the load carrying capacity of steel tubular columns in-filled with fibre reinforced concrete is greater than the conventional concrete. Eurocode 4 predicts the best estimation for CFST sections both conventional and fibre reinforced concrete columns. Hence this investigation would give a solution for effective application of fibre reinforced concrete in steel tubular sections to increase the load carrying capacity.